Strategic Thinking and Merit Understanding of Public Employees During The Covid-19 Pandemic - Onur Akçakaya; Gökhan Acar (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Today, strategic management emerges as a crucial element in achieving the sustainability goals of nation-states. In addition, the importance of qualified public staff who will implement these plans is an indisputable fact for reflecting the strategic foresight made to take decisive and urgent measures against sudden epidemics and disasters. This study aims to reveal the relationship between strategic management and merit understanding of public employees during the Covid-19 pandemic. In the analysis of the study data, arithmetic mean, frequency, standard deviation and percentage values, which are descriptive statistics, were examined. For determining if it is necessary to perform parametric analyzes for this study, first, an examination was made on whether the scale data shows a normal distribution. In this study, the descriptive research method was used, and data collection was made with the help of a questionnaire. When we look at the study results, the strategic management perceptions of public employees are at a high level as per the results obtained in the resource and environment dimensions. Besides, as per the general average and merit dimension, training dimension, assignment dimension and overall evaluation results of the answers related to the merit understanding of the public employees participating in the study, their merit understanding is at a high level. In conclusion, it is aimed to determine a method and form a theoretical basis according to the study results of decision makers, strategy makers, and public employees' understanding of strategic management and merit.